Risk Factors for Working Pregnant Women and Potential Adverse Consequences of Exposure: A Systematic Review - María del Rocío Corchero-Falcón; Juan Gómez-Salgado; Juan Gómez-Salgado; Juan Jesús García-Iglesias; Juan Carlos Camacho-Vega; Javier Fagundo-Rivera; Ana María Carrasco-González (Frontiers Media S.A., 2023)
Objective: To assess the risk factors perceived as stressors by pregnant women in the work environment and the possible adverse consequences of such exposure for the normal development of pregnancy.Methods: Systematic review, guided by the PRISMA guidelines, and using Pubmed, Web of Science, Dialnet, SciELO, and REDIB databases. Methodological quality was assessed using the critical appraisal tools for non-randomised studies of the Joanna Briggs Institute.Results: A total of 38 studies were included. The main risk factors found in the work environment of pregnant women were chemical, psychosocial, physical-ergonomic-mechanical factors, and other work-related factors. The main adverse consequences of exposure to these factors include low birth weight, preterm birth, miscarriage, hypertension and pre-eclampsia, as well as various obstetric complications.Conclusion: During pregnancy, working conditions that are considered acceptable in normal situations may not be so during this stage due to the major changes that occur during pregnancy. Many obstetric effects may have an important impact in the mother's psychological status; therefore, it is important to optimise working conditions during this stage and to reduce or eliminate possible risks.